The man question : male subordination and privilege - Dowd, Nancy E., 1949- (New York : New York University Press, 2016)
In this work, feminist legal theorist Nancy Dowd exhorts readers to apply the anti-essentialist model - so dominant in feminist jurisprudence - to the study of masculinities.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Men -- Legal status, laws, etc; Sex and law; Masculinity; Fatherhood; Feminist theory; Society; Society & culture: general; Feminism & feminist theory; Gender studies: men & boys; "Gender studies: transgender, transsexual, intersex people".; Law